Clickbait Headline and Its Threat in The National Resilience - M. Rizky Kertanegara (CoverAge: Journal of Strategic Communication, 2018)
Since the emergence of Internet technology, the information that goes into the audience through online media becomes more abundant. Therefore, news content producers, both traditional and emerging media, are turning to online media to present the news that interests the audience in order to survive in the midst of intense business competition. Key Performance Indicators (KPI) become the success parameters of news widely clicked, read, or shared on their social media platform. This phenomenon then gave rise to Clickbait Headline, a unique and eyecatching type of news title. However, the clickbait headline has frequently used to deliver manipulative articles. One of the concerns of the author is the rise of media that lifts Islamic content using this clickbait headline strategy. Some of these media make clickbait headline that glorifies things related to Islam. This phenomenon could be the threat to the national resilience of Indonesia in the midst of the polarization of society due to differences of political views. To that end, all stakeholders (government, media, and netizen) must be responsible in increasing the digital media literacy for responding the phenomena of clickbait headline.